Recycling spodumene flotation tailings in cement mortar: A synergy with metakaolin. (1st October 2021) - Yang, Jie; Wu, Houqin; Tang, Zhen; Huo, Xiaomei; Lu, Jiahui; Xu, Longhua
Graphical abstract: Highlights: The mechanical properties of cement mortar could be reduced by the formation of Hadley grains. The optimization of particle size distribution was helpful to improve the mechanical properties. Improved pozzolanic activity of minerals was also helpful for the mechanical properties. Mica in SFT was harmful to the mechanical properties of mortar. Abstract: Using industrial by-products as a substitute for conventional natural resources in construction materials is of interest to practitioners of environment preservation and solid wastes management. In this paper, spodumene flotation tailings (SFT) were employed to replace aggregate such as standard sand (SS) to prepare cement mortar. Besides, metakaolin (MK) was adopted as cementitious material participating in hydration reaction to improve the mechanical properties of cement mortar. Some tests such as BET, optical microscope, SEM-EDS, XRD, FT-IR, and XPS were performed to speculate the strengthening mechanism with the addition of MK and SS. SFT and SS are crystalline and primarily act as unreactive fillers. However, they could change the internal hydration environment, such as pore distribution, and thus influence the hydration products and the mechanical properties of cement mortar.